2016
DOI: 10.1177/0886260516659654
|View full text |Cite
|
Sign up to set email alerts
|

Parental Physical Force and Alcohol Use in Emerging Adults: Mediation by Psychological Problems

Abstract: Research has indicated that negative parenting practices, such as physical punishment, are associated with negative outcomes in children. These negative outcomes can present during childhood and during emerging adulthood. One negative consequence can be excessive alcohol use, a problematic outcome with its own myriad consequences. The goal of the current study was to examine the effects of parental physical force on emerging adult functioning, specifically alcohol and psychological problems. A sample of 488 yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…For example, in a study conducted by McKinney, Walker, and Kwan (2020), 59% of emerging adults surveyed endorsed receiving physical punishment from their father within the past year. In another study, 20% of emerging adult males and 17% of females reported experiencing corporal punishment (Pollard & McKinney, 2019). More recently, a study found that 30.9% of male and 20.9% of female emerging adults reported being spanked by their fathers and 33.9% of males and 28% of females reported being spanked by their fathers in the past year (McKinney, Stearns, & Rogers, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…For example, in a study conducted by McKinney, Walker, and Kwan (2020), 59% of emerging adults surveyed endorsed receiving physical punishment from their father within the past year. In another study, 20% of emerging adult males and 17% of females reported experiencing corporal punishment (Pollard & McKinney, 2019). More recently, a study found that 30.9% of male and 20.9% of female emerging adults reported being spanked by their fathers and 33.9% of males and 28% of females reported being spanked by their fathers in the past year (McKinney, Stearns, & Rogers, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Despite evidence linking physical discipline methods to harmful outcomes in earlier developmental periods (Gershoff & Grogan-Kaylor, 2016) and the influence of parents in emerging adulthood (Donnelly et al, 2013;McKinney & Renk, 2008), very little appears to be known about how parents discipline their emerging adult children. McKinney and colleagues (i.e., McClelland & McKinney, 2016;McKinney & Brown, 2017;McKinney, Brown, & Malkin, 2018;McClelland & McKinney, 2016;McKinney, Stearns, & Szkody, 2018;McKinney, Walker, and Kwan, 2016;Pollard & McKinney, 2016) have frequently used the CTSPC (Straus et al, 1998) to assess parental use of inductive tactics, psychological aggression, and physical punishment (i.e., physical assault and/or corporal punishment) during emerging adulthood. Although they generally found low rates of parental psychological aggression and physical assault, a significant portion of their samples (i.e., >5%) reported extremely high rates of these behaviors and concurrent high rates of psychological problems.…”
Section: Discipline In Emerging Adulthoodmentioning
confidence: 99%
“…Thus, although emerging adults can still experience ODD problems, they may differ between males and females and more research is needed to better understand these differences, particularly in the context of parental psychopathology and maltreatment. For example, research has indicated that sons are more likely to experience physical maltreatment from their parents, and this risk may be stronger in conjunction with parental anxiety and depressive problems, thus causing males to act out more and display ODD problems (Pollard & McKinney, 2016). Given that maltreatment by parents may be one of the processes through which parental anxiety and depressive problems can influence emerging adult ODD problems, including defiance and irritability, as well as associated gender differences, it is important to investigate this mediational process in the context of parent and child gender.…”
Section: Odd Problems In Emerging Adulthood and Gendermentioning
confidence: 99%